2021
DOI: 10.5826/dpc.1103a54
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Onset Acral Pigmented Macules: An Innocuous Diagnosis

Abstract: A 60-year-old healthy man presented with sudden onset of asymptomatic, brown-black macules over his feet soles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…described brown dots and globules of bizarre shapes having a stuck‐on appearance, whereas brown dots, globules and criss‐cross lines have been reported by Amrani et al 122,123 . Finally, Jindal et al 120 . revealed the presence of orange‐brown streaks having ridge enhancement pattern (Fig.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…described brown dots and globules of bizarre shapes having a stuck‐on appearance, whereas brown dots, globules and criss‐cross lines have been reported by Amrani et al 122,123 . Finally, Jindal et al 120 . revealed the presence of orange‐brown streaks having ridge enhancement pattern (Fig.…”
Section: Resultsmentioning
confidence: 85%
“…Cydnidae bugs, also known as the burrower bug, belong to Chilocoris species that usually live inside the soil feeding on the roots of underground plants. When accidentally crushed, they release an orange‐brown pigment that stains the skin 120 . These pigmented macules should be distinguished by other pigmented lesions, including acral melanoma.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four single reports described dermoscopic features of cydnidae pigmentation [57][58][59][60].The main feature consisted of brown dots/globules and/or lines [57,59,60]. Additionally, Jindal et al observed the presence of orange-brown structureless areas with ridge enhancement over the sole, thereby suggesting that the pigment released by the bug seeps through the skin dermatoglyphics [58].…”
Section: Cydnidae Pigmentationmentioning
confidence: 99%